Evaluation of Use of Intensive Care Unit (ICU) Scoring Systems among Healthcare Professionals: Intensive Care Unit Scoring Systems Evaluation - Jahangir, Aneela; Saba, Noor-Us-; Raza, Madiha; Hyder, Furkan; Sultan, Syed Farjad (Pakistan Journal of Health Sciences, 2025)
The prognosis of patients in the Intensive Care Unit (ICU) is a matter of worry for critically ill patients, their families, and healthcare personnel. However, predicting the chances of recovery in the ICU can be challenging. Scoring systems serve as standardized instruments utilized in critical care research to determine which patients should be included in a study and to establish the comparability of different patient groups. Objective: To determine the frequency of use of Scoring Systems to predict the outcome of critically ill patients in the intensive care units of Pakistan. Methods: This cross-sectional study was conducted in all the healthcare institutions of Pakistan that are recognized by CPSP for fellowship in ICU training, from 10th April 2018 till 10th October 2018. Forty-one ICU physicians were included. Pre-designed questionnaires were sent to these physicians. Results: Out of 41 physicians, 33 (80.5%) of them used and 8 (19.5%) did not use ICU scoring systems. Only 3 consultants reported the use of Anatomical scoring systems. GCS was the most used Disease Specific Scoring System (97.5%), followed by Child Pugh’s Score (80%) and Ranson’s Criteria (70%). 50% reported the use of Sequential Organ Failure Assessment (SOFA) and 42% used Multiple Organ Dysfunction Score (MODS). 63% used Acute Physiology and Chronic Health Evaluation (APACHE). 93% did not use any Therapeutic Weighted Score. 77.5% used Richmond Agitation-Sedation Scale (RASS) and 25% used Ramsey’s. Conclusion: It was found that 80.5% physicians used ICU scoring systems to assess mortality and severity of illness.